Learning processes as mediators of the impact of workplace coaching interventions on goal attainment - Conny H. Antoni; Alexandra Tatar (Journal of Occupational and Organizational Psychology, 2025)
This study contributes to research on how workplace coaching works by examining learning processes as a mediating mechanism of the impact of problem-specific interventions on goal attainment. This has rarely been investigated. Fifty-five coach–coachee dyads with 51 coaches and 55 coachees participated in the study. Workplace coaching lasted seven to eight coaching sessions in average. Coaches and coachees gave ratings in each session. We analysed this data (NLevel20.167em=0.167em55, NLevel10.167em=0.167em335–407) using longitudinal multilevel structural equation modelling accounting for the nested data structure. As expected, coachees' perceived goal attainment increased throughout the coaching process. The results of the study also revealed the mediating role of learning processes in the impact of problem-specific interventions, specifically clarification of meaning and mastery/coping, and, but to a lesser extent, implementation actuation, on goal attainment in coaching. Data for all hypothesised models showed a good or acceptable model fit. In contrast, the model fit was poor, when we explored differential mediation effects, which supported only single-loop learning as a mediator. These results underscore the importance of stimulating learning processes through specific interventions to improve the effectiveness of workplace coaching.
Keywords: 650; clarification of meaning; coaching effectiveness; coaching processes; common factors; implementation actuation; mastery/coping